Kaitan riset akuntansi dengan pengajaran dan praktik: pendekatan teori positif - Arif Budiarto (Jurnal Akuntansi dan Auditing Indonesia, 1999)
There has been a fundamental change in accounting ought to be done to positive or descriptive theories of why it is done as it is. Several years ago, accounting students learned normative theories of accounting but today, analogical reasoning is not the only way to make an accounting policy recommendation. The study of descriptive theories and extent rules will prepare students to evaluate alternatives in the face of inevitable change in the social, economic, and political environment. I believe that there has been a fundamental change in accounting research and education which has an influence on the reason for changing current practices. This paper presents the change in the form of "accounting theory." Specifically, the shift from normative theories to pisitive theories.